Suitability model development for rooftop rainwater harvesting (RRWH) system in an urban area using geographical information systems - Mohd Radzali, Nurul Ain Wahida; Mohd Shafri, Helmi Zulhaidi; Yusuf, Badronnisa; Mohamed Rehan, Balqis (Prince of Songkla University, 2023)
A Rooftop Rainwater Harvesting (RRWH) system may improve water security as it allows water collection to be done directly at home, especially in an urban area. Geographical Information System (GIS) approach has been utilized in this study as a platform for urban environmental analysis, in which the suitability of the rooftop as a catchment area for RRWH system in terms of quality and quantity were evaluated. The GIS model was developed to simulate and predict the suitability of rooftop based on its estimated volume of collected rainwater and Water Index Quality (WQI). Furthermore, weightages for several criteria such as roof material (RM), roof condition (RC), roof area (RA) and runoff coefficient (RuCO) have been determined using an Analytical Hierarchy Process (AHP). Then, Weighted Linear Combination (WLC) was applied to aggregate all these criteria according to their significance. The final map produced from the developed suitability model for RRWH system was quantized into three categories: highly suitable, moderately suitable, and not suitable. The results demonstrate that asbestos is not suitable with a total of 53, concrete is moderately suitable with the total of 178, and metal is highly suitable with the total of 150; for use in rooftop rainwater harvesting. Overall, this study showed that the study area is moderately suitable for RRWH system adoption